Cardiorespiratory alterations following intermittent photostimulation of RVLM C1 neurons: Implications for long-term blood pressure, breathing and sleep regulation in freely moving rats - Toledo, Camilo; Andrade, David C.; Diaz-Jara, Esteban; Ortolani, Domiziana; Bernal-Santander, Ignacio; Schwarz, Karla G.; Ortiz, Fernando C.; Marcus, Noah J.; Oliveira, Luiz M.; Takakura, Ana C.; Moreira, Thiago S.; Del Rio, Rodrigo (My University, 2022)
Aim Sympathoexcitation and sleep-disordered breathing are common contributors for disease progression. Catecholaminergic neurons from the rostral ventrolateral medulla (RVLM-C1) modulate sympathetic outflow and have anatomical projections to respiratory neurons; however, the contribution of highly selective activation of RVLM-C1 neurons on long-term autonomic and breathing (dys)regulation remains to be understood. Methods To explore this relationship, a lentiviral vector carrying the light-sensitive cation channel channelrhodopsin-2 (LVV-PRSX8-ChR2-YFP) was unilaterally injected into the RVLM of healthy rats. On the contralateral side, LVV-PRSX8-ChR2-YFP was co-injected with a specific immunotoxin (D beta H-SAP) targeted to eliminate C1 neurons. Results Intermittent photostimulation of RVLM-C1 in vivo, in unrestrained freely moving rats, elicited long-term facilitation of the sympathetic drive, a rise in blood pressure and sympatho-respiratory coupling. In addition, photoactivation of RVLM-C1 induced long-lasting ventilatory instability, characterized by oscillations in tidal volume and increased breathing variability, but only during non-rapid eye movement sleep. These effects were not observed when photostimulation of the RVLM was performed in the presence of D beta H-SAP toxin. Conclusions The finding that intermittent activation of RVLM-C1 neurons induces autonomic and breathing dysfunction suggest that episodic stimulation of RVLM-C1 may serve as a pathological substrate for the long-term development of cardiorespiratory disorders.
Keywords: brainstem sympathetic neurons; breathing irregularity; cardiorespiratory control; rvlm-c1 neurons